The Effectiveness of Warm Water Foot Soak Therapy and Rose Aroma Therapy on Lowering Blood Pressure and Anxiety in Hypertensive Patients : Literature Review - Muhith, Abdul; Subairi, Moh; Mampesi, Anastasa; Oliveira, Adirson Barbosa de; Zulkarnain, Eva Vera; Mahyuvi, Tata; Fatkan, Moch; Muthoharoh, Anies (Chakra Brahmanda Lentera Institute, 2024)
Background: Hypertension is a disease that can cause anxiety for sufferers, this is because the disease is the main factor in the occurrence of other diseases such as stroke, this must be treated immediately by doing a combination of non-pharmacological and pharmacological treatment to reduce symptoms and complications that may occur. The purpose of this literature review is to determine the effectiveness of warm water foot soak therapy and the administration of rose aroma therapy on reducing blood pressure and anxiety in hypertensive patients Methods: The method used PRISMA Approach for this article is literature review using a journal database from Google Scholar in the period of 2018-2023 with search keywords namely